Pengaruh Tourist Attraction, Tourist Happiness dan Memorable Tourism Experience terhadap Revisit Intention Pengunjung pada Wisata Cafe Sahabat Sejati Kabupaten Kediri - Dewi Ayu Puspita Sari; Ahmad Idris; Beni Mahyudi S (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to determine the influence of Tourist Attraction, Tourist Happiness, and Memorable Tourism Experience on Revisit Intention of visitors at Cafe Sahabat Sejati in Kediri Regency. This research employs a quantitative method using a survey approach with questionnaires distributed to 55 respondents who have visited the cafe more than once. The sampling technique used is purposive sampling. The results indicate that Tourist Attraction significantly influences Revisit Intention, Tourist Happiness significantly influences Revisit Intention, and Memorable Tourism Experience significantly influences Revisit Intention. Simultaneously, these three variables have a significant impact on visitors' revisit intention. The findings of this study are expected to serve as a reference for Cafe Sahabat Sejati management in enhancing tourist attraction quality, visitor experience, and overall comfort to increase return visits.